Field testing a protocol to facilitate the involvement of pharmacists in community based palliative care - Jiwa, Moyez; Hughes, Jeffery; O'Connor, Moira; Tuffin, P. (Pharmaceutical Society of Australia, 2012)
Most palliative care patients and their carers will interact with a pharmacist, particularly when obtaining medication during their illness. Pharmacists working in the community do not have a formal role in the care of patients who are receiving palliative care. Objective: The aim of this study was to field test a protocol to coordinate a formal medication management review of palliative care patients by an accredited pharmacist. Methods: Eligible patients resident in the community were recruited by a palliative care nurse. Patients consented to a formal review of their medication by an accredited pharmacist. The request for the review was endorsed by the patient’s doctor. One accredited pharmacist, from a list of 18 accredited pharmacists who had attended a short course on palliative care and who had access to an experienced palliative care pharmacist, reviewed the medication at the patient’s residence. The pharmacist then reported their recommendations to a project manager who passed them back to the doctor. Patients and relatives were able to consult the pharmacist if they required further help for a number of weeks post-review.Results: Forty patients and 13 pharmacists participated over a four month period. Between two and 30 days elapsed from patient consent to the pharmacist’s report to the referring doctor (M = 10.6 days, SD = 6.0). Thirteen pharmacists conducted 0–9 reviews each and made 145 recommendations. Only three pharmacists recorded post-review patient interactions in diaries. Out of all interactions that took place between these three pharmacists and corresponding patients, almost half were initiated by the pharmacist. These were used mainly to share or request information, although two resulted in medication changes. Experts in palliative care and the patients were generally very positive about the results of the medication review. Conclusions: An innovation that builds on the existing system for Medication Management Review to engage with patients in palliative care is valuable. This project was an important first step in developing a suitable protocol. In this case the protocol was only partially successful although the project contributes to existing knowledge and understanding in this area.